Sustainability Performance Commitment and Market Liquidity: An Event study analysis - Maina, Purity (Acta Carolus Robertus, 2024)
This study investigates the impact of voluntary commitments to the Sustainable Stock Exchange Initiative (SSEI) on market liquidity within African Security Exchanges amid an increasing global focus on sustainability in capital markets. While adopting the event study methodology, the study utilised the Paired T-test and the two-way fixed effect panel model to analyse the short- and medium-term market liquidity effects of 13 Security Exchanges. The findings revealed significant short-term market liquidity improvements, which diminished over time. These results highlight the importance of policy recommendations that offer insights for security exchange policymakers as they adapt to sustainability dynamics and strive to enhance market performance. The study suggests that exchanges adopt concrete strategies to maintain market liquidity improvements, such as incentivisation schemes for listed companies to enhance their long-term sustainability performance and comprehensive measures addressing other underlying factors influencing market liquidity. Further, security exchanges should continue developing investor education programs on sustainability to enhance awareness and implement more sustainable initiatives to enhance investor confidence and meet the growing demand for responsible investment.